Working with the elephant : methods for engaging with the unsaid in groups and organizations - Svalgaard, Lotte (Routledge, 2025)
"We've all been there. We are in a working group or at a meeting, discussing a topic or a challenge, and all the while, as a separate track running underneath our conversation, there is a subtext that no one explicitly addresses. This is an example of 'the elephant in the room.' Most of us notice the elephant, it gets in the way, and it's difficult to deal with until someone points at it and says, 'There it is, let's take a look at it and reduce its impact.' With an engaging use of examples and questions, Lotte Svalgaard addresses how we can best deal with the elephant and thus promote job satisfaction, creativity and productivity. In the context of action, what we notice often recedes into the background and gradually slips out of focus until we eventually reconnect with our need to reflect and recreate a space for it. This book addresses the challenge of focusing on, holding on to and acting on what we notice 'in the middle of it all'. Maintaining a simultaneous focus on task and process - what we do and what we notice - is what I define as 'double awareness'. Double awareness is not only a core capacity but also a core challenge. While the aim of The Elephant in the Room was to promote understanding and awareness of this core challenge and to inspire both reflection and action for anyone wishing to improve engagement in their workplaces, Working with the Elephant is taking this challenge a step further by providing 10 core challenges in dealing with elephants in groups and organizations. It is a workbook about the difficult transition from avoidance to action. With help, support and tips, it guides readers to take action where it will make a difference for them, their group and the organization as a whole. It can be used as a workbook for The Elephant in the Room or it can be used independently"--